A whitefly effector Bsp9 targets host immunity regulator WRKY33 to promote performance. (14th January 2019) - Wang, Ning; Zhao, Pingzhi; Ma, Yonghuan; Yao, Xiangmei; Sun, Yanwei; Huang, Xiande; Jin, Jingjing; Zhang, Youjun; Zhu, Changxiang; Fang, Rongxiang; Ye, Jian
Abstract : Whiteflies, Bemisia tabaci (Hemiptera), are pests causing economic damage to many crops, capable of transmitting hundreds of plant vector-borne viruses. They are believed to secrete salivary protein effectors that can improve vector colonization and reproductive fitness in host plants. However, little is known about effector biology and the precise mechanism of action of whitefly effectors. Here, we report a functional screening of B. tabaci salivary effector proteins (Bsp) capable of modulating plant innate immunity triggered by plant endogenous pattern peptide Pep1. Four immunity suppressors and two elicitors were identified. Bsp9, the most effective immunity suppressor, was further identified to directly interact with an immunity regulator WRKY33. We provide evidence that Bsp9 may suppress plant immune signalling by interfering with the interaction between WRKY33 and a central regulator in the MAPK cascade. The interference by Bsp9 therefore reduces plant resistance to whitefly by inhibiting activation of WRKY33-regulated immunity-related genes. Further detailed analysis based on transgenic plants found that whitefly effector Bsp9 could promote whitefly preference and performance, increasing virus transmission. This study enriches our knowledge on insect effector biology. This article is part of the theme issue 'Biotic signalling sheds light on smart pest management'.